Is aromatic plants environmental health engineering (APEHE) a leverage point of the earth system? - MengYu Lu (Heliyon, 2024)
It is important to note that every ecological niche in an ecosystem is significant. This study aims to assess the importance of medicinal and aromatic plants (MAPs) in the ecosystem from multiple perspectives. A primary model of Aromatic Plants Environmental Health Engineering (APEHE) has been designed and constructed. The APEHE system was used to collect aerosol compounds, and it was experimentally verified that these compounds have the potential to impact human health by binding to AKT1 as the primary target, and MMP9 and TLR4 as secondary targets. These compounds may indirectly affect human immunity by reversing drug resistance in drug-resistant bacteria in the nasal cavity. This is mainly achieved through combined mutations in sdhA, scrA, and PEP. Our findings are based on Network pharmacology and molecular binding, drug-resistance rescue experiments, as well as combined transcriptomics and metabolomics experiments. It is suggested that APEHE may have direct or indirect effects on human health.We demonstrate APEHE's numerous potential benefits, such as attenuation and elimination of airborne microorganisms in the environment, enhancing carbon and nitrogen storage in terrestrial ecosystems, promoting the formation of low-level clouds and strengthening the virtuous cycle of Earth's ecosystems. APEHE also supports the development of transdisciplinary technologies, including terpene energy production. It facilitates the creation of a sustainable circular economy and provides additional economic advantages through urban optimisation, as well as fresh insights into areas such as the habitability of other planets. APEHE has the potential to serve as a leverage point for the Earth system. We have created a new research direction.